Los conocimientos teóricos - técnicos, metodológicos, materiales e instrumentos en el proceso enseñanza - aprendizaje de la cultura estética: dibujo artístico, en los niños y niñas del séptimo grado de la escuela de educación básica “IV Centenario N° 2”, parroquia Sucre, cantón y provincia de Loja, periodo lectivo 2012-2013 - Ojeda Cabrera, Julio César (2014)
The research makes reference to: THEORETICAL - TECHNICAL, METHODOLOGICAL KNOWLEDGE, MATERIALS AND INSTRUMENTS IN THE TEACHING - LEARNING PROCESS OF AESTHETIC CULTURE: ARTISTIC DRAWING, IN CHILDREN OF SEVENTH YEAR OF THE SCHOOL OF BASIC EDUCATION “IV CENTENARIO N° 2”, PARROQUIA SUCRE, CANTÓN LOJA, PROVINCIA DE LOJA, ACADEMIC PERIOD 2012-2013. The overall objective was aimed at contribute to the improvement of the teaching - learning process of aesthetic culture: artistic drawing, for children of School of Basic Education "IV Centenario No. 2", through the diagnosis and the contribution of a pedagogical updated proposal. It is thought that artistic education does not work and it is not perceived as something useful; that it is not a profession or it is not a serious study, that is, it is thought that; it should be another safer profession like lawyer, architect, doctor, etc., a career to survive, which is not true, thus, the drawing, at the same time sets an idea, communicates and reports the structure with which each person captures the phenomenon, simultaneously reflected in the symbolic value although it assumes. Its greater complexity is given by the character of the drawings’ representations. The value that is acquired like a way of sensible apprehension and the objects is what confers its key role in the knowledge of things. For this reason there are many frustrated artists who are restricted in their creativity, their innate gifts; in a word his life.The present research is descriptive type, explanatory based on the achievement of specific objectives and framed within the qualitative paradigm; in addition the following methods were used: scientific method, descriptive method, analytical method - synthetic, hypothetical - deductive method, Among the techniques that were employed are the survey that was applied to the teachers and children of the educational institution, to obtain direct information, to have an approach of this problem that affects the teaching - learning process of artistic design, and the population with which it worked was two teachers of the subject of aesthetic culture and 24 students of seventh year of basic education. With the obtained information, after the field work it was concluded that the teachers at "IV Centenario N º 2" school, of Basic Education give the appropriate importance to the subject of aesthetic culture, since the same helps to the development of skills and abilities of children of seventh year of basic education, in the same way, it recommends to teachers to promote discussions with children in the classroom (about the importance of aesthetic culture), in order to inculcate the practice of artistic drawing